Tailoring the sampling time of single-sample GFR measurement according to expected renal function: a multisite audit - Helena McMeekin; Sam Townrow; Mark Barnfield; Andy Bradley; Ben Fongenie; Daniel R. McGowan; Matthew Memmott; Charlotte A. Porter; Fred Wickham; Nick Vennart; Maria Burniston (EJNMMI Physics, 2022)
Abstract Background The 2018 BNMS Glomerular Filtration Rate (GFR) guidelines recommend a single-sample technique with the sampling time dictated by the expected renal function, but this is not known with any accuracy before the test. We aimed to assess whether the sampling regime suggested in the guidelines is optimal and determine the error in GFR result if the sample time is chosen incorrectly. We can then infer the degree of flexibility in the sampling regime. Methods Data from 6328 patients referred for GFR assessment at 6 different hospitals for a variety of indications were reviewed. The difference between the single-sample (Fleming) GFR result at each sample time and the slope–intercept GFR result at each hospital was calculated. A second dataset of 777 studies from one hospital with nine samples collected from 5 min to 8 h post-injection was analysed to provide a reference GFR to which the single-sample results were compared. Results Recommended single-sample times have been revised: for an expected GFR above 90 ml/min/1.73m2 a 2-h sample is recommended; between 50 and 90 ml/min/1.73m2 a 3-h sample is recommended; and between 30 and 50 ml/min/1.73m2 a 4-h sample is recommended. Root mean square error in single-sample GFR result compared with slope–intercept can be kept less than or equal to 3.30 ml/min/1.73m2 by following these recommendations. Conclusion The results of this multisite study demonstrate a reassuringly wide range of sample times for an acceptably accurate single-sample GFR result. Modified recommended single-sample times have been proposed in line with the results, and a lookup table has been produced of rms errors across the full range of GFR results for the three sample times which can be used for error reporting of a mistimed sample.